(untitled) (Journal of Comparative & International Higher Education, 2023)
In this study, we present the results of a project, which involved students enrolled at four universities located in Ecuador, Dominican Republic, Czech Republic, and the United Kingdom. The main goal of the project was to raise students’ awareness about the conditions that cause epistemic injustice for migrants and refugees. Epistemic injustice is a concept that sheds light on the ethical dimensions of our epistemic practices. It recognizes that individuals can be wronged specifically in their capacity as knowers, a capacity essential to human value (Fricker, 2007). The project material included a set of interviews with migrants and refugees as well as desk research about the status of their national migratory contexts. Students exchanged their testimonies via extended sessions that took place between October and November of 2022. An ethics of listening was cultivated to disrupt conventions of authorized discourse about migrants. Through understanding that labels such as illegal, undocumented and unauthorized are not neutral descriptors but carry implicit association and value judgments that frame and influence debate, students were invited to engage in a form of communication and consciousness to create spaces for unheard, marginalized voices of migration trends (Lipari, 2010.) Our international research with students and migrants was influenced by Arjun Appadurai (2006) who invites us to question established paradigms and critically reflect on contemporary global dynamics of migration contributing to Sousa Santos ‘ecology of knowledges’ across continents and cultures (2015).